Effect of Morning Light Glasses and Night Short-Wavelength Filter Glasses on Sleep-Wake Rhythmicity in Medical Inpatients - Formentin, Chiara (Front Physiol, 2020)
Sleep and circadian rhythm disorders are common amongst medical inpatients. They are caused by a mixture of factors, including noise, loss of habitual daily routines, and abnormal exposure to light, which tends to be insufficient in the day and too high at night. The aim of the present study was to test the efficacy of morning light therapy plus night short-wavelength filter glasses on sleep quality/timing, and sleepiness/mood over the daytime hours, in a group of well-characterized medical inpatients. Thirty-three inpatients were enrolled and randomized (2:1) to either treatment (n = 22; 13 males, 48.3 ± 13.3 years) or standard of care (n = 11; 8 males, 56.9 ± 12.9 years). On admission, all underwent a baseline assessment of sleep quality/timing and diurnal preference. During hospitalization they underwent monitoring of sleep quality/timing (sleep diaries and actigraphy), plus hourly assessment of sleepiness/mood during the daytime hours on one, standard day of hospitalization. Patients in the treatment arm were administered bright light through glasses immediately after awakening, and wore short-wavelength filter glasses in the evening hours. Treated and untreated patients were comparable in terms of demographics, disease severity/comorbidity, diurnal preference and pre-admission sleep quality/timing. During hospitalization, sleep diaries documented a trend for a lower number of night awakenings in treated compared to untreated patients (1.6 ± 0.8 vs. 2.4 ± 1.3, p = 0.057). Actigraphy documented significantly earlier day mode in treated compared to untreated patients (06:39 ± 00:35 vs. 07:44 ± 00:40, p = 0.008). Sleepiness during a standard day of hospitalization, recorded between 09:30 and 21:30, showed physiological variation in treated compared to untreated patients, who exhibited a more blunted profile. The level of sleepiness reported by treated patients was lower over the 09:30–14:30 interval, i.e., soon after light administration (interaction effect: F = 2.661; p = 0.026). Mood levels were generally higher in treated patients, with statistically significant differences over the 09:30–14:30 time interval, i.e., soon after light administration (treatment: F = 5.692, p = 0.026). In conclusion, treatment with morning bright light and short-wavelength filter glasses in the evening, which was well tolerated, showed positive results in terms of sleepiness/mood over the morning hours and a trend for decreased night awakenings.